Kidney Transplantation From Hepatitis B Surface Antigen (HBsAg)–Positive Living Donors to HBsAg-Negative Recipients: Clinical Outcomes at a High-Volume Center in China. (26th February 2020) - Wang, Xian-ding; Liu, Jin-peng; Song, Tu-run; Huang, Zhong-li; Fan, Yu; Shi, Yun-ying; Chen, Li-yu; Lv, Yuan-hang; Xu, Zi-lin; Li, Xiao-hong; Wang, Li; Lin, Tao
Abstract: Background: Data on kidney transplantation (KTx) from hepatitis B surface antigen (HBsAg)–positive (HBsAg+) donors to HBsAg-negative (HBsAg−) recipients [D(HBsAg+)/R(HBsAg-)] are limited. We aimed to report the outcomes of D(HBsAg+)/R(HBsAg−) KTx in recipients with or without hepatitis B surface antibody (HBsAb). Methods: Eighty-three D(HBsAg+)/R(HBsAg−) living KTx cases were retrospectively identified. The 384 cases of KTx from hepatitis B core antibody–positive (HBcAb+) living donors to HBcAb-negative (HBcAb−) recipients [D(HBcAb+)/R(HBcAb−)] were used as the control group. The primary endpoint was posttransplant HBsAg status change from negative to postive (-− →+). Results: Before KTx, 24 donors (28.9%) in the D(HBsAg+)/R(HBsAg−) group were hepatitis B virus (HBV) DNA positive, and 20 recipients were HBsAb−. All 83 D(HBsAg+)/R(HBsAg−) recipients received HBV prophylaxis, while no D(HBcAb+)/R(HBcAb−) recipients received prophylaxis. After a median follow-up of 36 months (range, 6–106) and 36 months (range, 4–107) for the D(HBsAg+)/R(HBsAg−) and D(HBcAb+)/R(HBcAb−) groups, respectively, 2 of 83 (2.41%) D(HBsAg+)/R(HBsAg−) recipients and 1 of 384 (0.26%) D(HBcAb+)/R(HBcAb−) became HBsAg+, accompanied by HBV DNA-positive ( P = .083). The 3 recipients with HBsAg−→+ were exclusively HBsAb−/HBcAb− before KTx. Recipient deaths were more frequent in the D(HBsAg+)/R(HBsAg−) group (6.02% vs 1.04%, P = .011), while liver and graft function, rejection, infection, and graft loss were not significantly different. In univariate analyses, pretransplant HBsAb−/HBcAb− combination in the D(HBsAg+)/R(HBsAg−) recipients carried a significantly higher risk of HBsAg−→+, HBV DNA−→+, and death. Conclusions: Living D(HBsAg+)/R(HBsAg−) KTx in HBsAb+ recipients provides excellent graft and patient survivals without HBV transmission. HBV transmission risks should be more balanced with respect to benefits of D(HBsAg+)/R(HBsAg−) KTx in HBsAb-/HBcAb− candidates. Abstract : Living D(HBsAg+)/R(HBsAg−) kidney transplantation in HBsAb+ recipients provides excellent graft and recipient survival without HBV (Hepatitis B Virus) infection. HBsAb−/HBcAb− in D(HBsAg+)/R(HBsAg−) recipients carried a higher risk of HBV infection and death. D(HBsAg+)/R(HBsAg−) should not be an absolute contraindication to kidney donation.